2015
DOI: 10.4093/dmj.2015.39.1.37
|View full text |Cite
|
Sign up to set email alerts
|

Appendicular Skeletal Muscle Mass and Insulin Resistance in an Elderly Korean Population: The Korean Social Life, Health and Aging Project-Health Examination Cohort

Abstract: BackgroundIncreasing evidence supports an association between age-related loss of muscle mass and insulin resistance. However, the association has not been fully investigated in the general population. Thus, we investigated the association between appendicular skeletal muscle mass (ASM) and insulin resistance in an elderly Korean population.MethodsThis cross-sectional study included 158 men (mean age, 71.8) and 241 women (mean age, 70.6) from the Korean Social Life, Health and Aging Project, which started in 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
75
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(83 citation statements)
references
References 38 publications
6
75
0
2
Order By: Relevance
“…Moreover, a HOMA-IR value higher than 2.3 increased in 3-4 times the risk of developing low relative ASM in a 4.6-years follow-up (Alemán-Mateo et al, 2014). Similarly, HOMA-IR ≥2.5 was identified as an important risk factor for sarcopenia in men aged 65 years or older (Kim et al, 2014) while, after adjusting by body weight, HOMA-IR was inversely associated with ASM in older men and women (Lee et al, 2015b). In fact, supporting a causal effect of insulin resistance on sarcopenia in the elderly, induction of insulin resistance in old rats by sucrose feeding results in significant loss of lean body mass, increase in fat mass and reduced muscle protein synthesis (Gatineau et al, 2015).…”
Section: Diabetesmentioning
confidence: 77%
“…Moreover, a HOMA-IR value higher than 2.3 increased in 3-4 times the risk of developing low relative ASM in a 4.6-years follow-up (Alemán-Mateo et al, 2014). Similarly, HOMA-IR ≥2.5 was identified as an important risk factor for sarcopenia in men aged 65 years or older (Kim et al, 2014) while, after adjusting by body weight, HOMA-IR was inversely associated with ASM in older men and women (Lee et al, 2015b). In fact, supporting a causal effect of insulin resistance on sarcopenia in the elderly, induction of insulin resistance in old rats by sucrose feeding results in significant loss of lean body mass, increase in fat mass and reduced muscle protein synthesis (Gatineau et al, 2015).…”
Section: Diabetesmentioning
confidence: 77%
“…These findings suggest that other factors such as physical activity might be more important than diet in relation to metabolic abnormalities among older adults [36], which is supported by the fact that age-related changes in body composition, especially increase in visceral fat, may elevate the risk of cardiometabolic disease [37]. In our study, individuals in the older age group who reported getting recommended physical activity levels had higher odds of MHO and lower odds of MONW phenotype (Supplemental Table S7).…”
Section: Discussionmentioning
confidence: 90%
“…At the limb level, lean body mass is synonymous with skeletal muscle mass, and the appendicular skeletal muscle mass (ASM) calculation was performed based on the sum of the lean body mass in all four limbs [20]. In our study, the muscle mass index (MMI) was derived by dividing ASM by weight in kg × 100, which is suggested to be a better predictor of insulin resistance and diabetes risk than ASM or height-adjusted ASM [11,13,[21][22][23].…”
Section: Methodsmentioning
confidence: 99%